Three-dimensional interconnected MoS2 nanosheets on industrial 316L stainless steel mesh as an efficient hydrogen evolution electrode. (15th January 2019) - Zhang, Kewei; Liu, Yanhong; Wang, Bo; Yu, Furong; Yang, Yalin; Xing, Lei; Hao, Jinhui; Zeng, Jun; Mao, Baodong; Shi, Weidong; Yuan, Shouqi
Abstract: The development of inexpensive and competent electrocatalysts for high-efficiency hydrogen evolution reaction (HER) has been greatly significant to realize hydrogen production in large scale. In this paper, we selected the inexpensive and commercially accessible stainless steel as the conductive substrate for loading MoS2 as a cathode for efficient HER under alkaline condition. Interconnected MoS2 nanosheets were grown uniformly on 316-type stainless steel meshes with different mesh numbers via a facile hydrothermal way. And the optimized MoS2 /stainless steel electrocatalysts exhibited superior electrocatalytic performance for HER with a low overpotential of 160 mV at 10 mA cm −2 and a small Tafel slope of 61 mV dec −1 in 1 M KOH. Systematic study of the electrochemical properties was performed on the MoS2 /stainless steel electrocatalysts in comparison with the commonly used carbon cloth to better comprehend the origin of the superior HER performance as well as stability. By collaborative optimization of MoS2 nanosheets and the cheap stainless steel substrate, the interconnected MoS2 nanosheets on stainless steel provide an alternative strategy for the development of efficient and robust HER catalysts in strong alkaline environment. Graphical abstract: Highlights: Industrial 316L stainless steel acts as a robust scaffold for HER in alkali. For the first time, mesh number of the substrate plays an important role for HER. The optimized MoS2 /stainless steel provides a η10 of 160 mV and good stability.